Inorganic A-site cations improve the performance of band-edge carriers in lead halide perovskites - Cheng Wang; Yaoguang Rong; Ti Wang (Frontiers of Optoelectronics, 2023)
Abstract In lead halide perovskites, organic A-site cations are generally introduced to fine-tune the properties. One of the questions under debate is whether organic A-site cations are essential for high-performance solar cells. In this study, we compare the band edge carrier dynamics and diffusion process in MAPbBr3 and CsPbBr3 single-crystal microplates. By transient absorption microscopy, the band-edge carrier diffusion constants are unraveled. With the replacement of inorganic A-site cations, the diffusion constant in CsPbBr3 increases almost 8 times compared to that in MAPbBr3. This work reveals that introducing inorganic A-site cations can lead to a much larger diffusion length and improve the performance of band-edge carriers. Graphical Abstract